2020
DOI: 10.1108/dprg-06-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ security and trust for online shopping after GDPR: examples from Poland and Ukraine

Abstract: Purpose This paper aims to consider the question of changes brought to consumers’ trust and security issues by the implementation of the General Data Protection Regulation (GDPR) in electronic commerce. Design/methodology/approach Online shopping policies in Poland and Ukraine are compared from the perspective of four factors as follows: application of terms of service and privacy policy, usage of online payment systems, presence in price comparison engines and grade of secure sockets layer security certific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The SCT denotes consumers’ sense of feeling when shopping online and cognizance that their personal information is safe from third parties [ 19 ]. Customers’ concerns about personal data leakage when using electronic platforms, specifically regarding financial issues, is one of the primary reasons deterring them from using electronic platforms amidst rapid, significant data developments [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCT denotes consumers’ sense of feeling when shopping online and cognizance that their personal information is safe from third parties [ 19 ]. Customers’ concerns about personal data leakage when using electronic platforms, specifically regarding financial issues, is one of the primary reasons deterring them from using electronic platforms amidst rapid, significant data developments [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seamless system operations enable customers to efficiently and quickly identify desired meals and place orders, elevating customer SAT. Strzelecki and Rizun [ 19 ] indicated that seamless and convenient application systems could provide users with a better experience, such as rapid screening, product and service comparison, and suitable product or service selection to increase loyalty and trust towards the application and propensity to reuse the platform. This study proposed the following hypothesis as visual and system design and information quality significantly affect consumers’ attitudes towards online food delivery services [ 23 , 24 ] following relevant research:…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, loyal customers help to promote the service providers and their brand image through their recommendations (Nghia et al., 2020). Loyal customers give referrals to encourage and attract more new customers to purchase or subscribe to the services (Strzelecki & Rizun, 2020). Furthermore, customer loyalty helps to reduce the service providers’ marketing cost (Kamath et al., 2019) as word of mouth is more effective (Tabrani et al., 2018) and trustworthy in portraying the essential services from certain service providers (Thiruvattal, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data diri seseorang menjadi tanggung jawab penting bagi semua pedagang atau produsen, konsumen akan merasa aman menggunakan e-commerce ketika data diri yang mereka gunakan terlindungi dan tidak bisa digunakan oleh pihak ketiga. Ketika transaksi online biasanya akan menampilkan layanan kebijakan privasi dan informasi kebijakan cookies jika ada yang menggunakannya (Strzelecki & Rizun, 2020).…”
Section: Pendahuluanunclassified